Production of alumina-graphene-copper hybrid composites by hot pressing technique: Investigation of mechanical, structural, and tribological properties (Mar, 10.1557/s43578-025-01551-5, 2025) - Macit, Cevher Kursat; Horlu, Merve; Tanyeri, Burak; Aksakal, Bunyamin (Springer Heidelberg, 2025)
[Abstract Not Available]